Study of knowledge, attitude, and practice regarding hepatitis B infection in first-degree relatives of patients suffering with hepatitis B infection - Jain, Ajay Kumar; Joshi, Amit D.; Jain, Deepika; Sircar, Shohini (International Journal Of Community Medicine And Public Health, 2023)
Background: Hepatitis B virus (HBV) infection is a significant public health problem in third-world countries, including India. The risk of infection among close family members of patients infected with chronic HBV infection is four to six times higher than in the general population. However, literature is scarce regarding the Knowledge, attitude, and practice toward HBV infection among the first-degree relatives of patients suffering from chronic hepatitis B. Hence, this study aimed to assess the knowledge, attitude, and practice regarding hepatitis B virus infection among first-degree relatives of hepatitis B patients. Methods: A cross-sectional, observational study was conducted amongst the 354 first-degree relatives of HBsAg-positive patients. A validated questionnaire consisted of twenty questions of knowledge, seven questions of attitude, and ten practice questions were employed to gather information. Results: The mean knowledge, attitude, and practice (KAP) were significantly better amongst participants aged 55-65 years and those who were educated. There was a positive correlation between knowledge and attitude (r=0.58, p value<0.05) and knowledge and practice (r=0.64, p value<0.05). Conclusions: There is insufficient knowledge regarding hepatitis B, its common symptoms, modes of transmission, and preventive tools among close relatives of patients suffering from chronic hepatitis B.